The Heart of the Good Institution
VI, 186 p.
Keywords: This book addresses the question: how can institutions develop and maintain a good purpose? And how can managers contribute to this endeavour? Twelve contributions explore this question, using MacIntyrean inquiry as a basis for exploring four main themes: Can management be considered a practice in the MacIntyrean sense? What is the role of specific virtues in the development of a virtuous institution? What are management vices and what are the conditions in which they flourish? And, can we use MacIntyrean ideas to consider the management of all forms of institutions? The volume is an international and multidisciplinary collection, with contributions from well-known writers in the field of management ethics, and innovative contributions that use MacIntyrean inquiry as a lens to examine fields such as hospitality, user generated music content and social sustainability. The papers are unified by their concern for the achievement of organizational excellence and integrity through ethical management. Unlike single author texts this edited volume brings together multiple perspectives on the topic of virtue ethics in management. In doing so, it explores the topic both more deeply and more widely than a single author can do. Because of its breadth, this book has the potential to become a turn-to research tool for those interested in virtue theory’s relevance to other academic interests such as organizational behavior (including motivation theory and social psychology), literature, contemporary social issue criticism, and business management.